Bufo praetextatus Boie, 1826 is a nomen dubium: an historical analysis of its original description supports the prevailing usage of Bufo japonicus Temminck & Schlegel, 1838 - Kaiser, Hinrich; Kaiser, Christine M.; Nishikawa, Kanto (Zootaxa, 2026)
The nomenclatural status of Bufo praetextatus Boie, 1826, described based on specimens collected by Jan Cock Blomhoff, has long been uncertain. Although this binomen has priority over the widely used B. japonicus Temminck & Schlegel, 1838, its application has been hindered by lost type material and misinterpretation of its original description. Through a detailed textual analysis of Boie’s work and corroboration from historical sources, we demonstrate that terms previously interpreted as type localities (“Vitikairu, Fikikojeru et Nakfudo”) are in fact phonetic transcriptions of vernacular Japanese names for toads. Furthermore, Boie’s description lists a broad distribution across Japan, not one restricted to Nagasaki. With Blomhoff’s collections including regions now known to be inhabited by three distinct, hybridizing species of Japanese Bufo (B. japonicus, B. formosus, B. torrenticola), it is impossible to determine which species Boie’s specimens represented. We therefore conclude that Bufo praetextatus Boie, 1826 must be considered a nomen dubium and that the prevailing use of B. japonicus should be maintained to ensure nomenclatural stability and accuracy.